Being Disoriented: Uncertain Encounters with Disability - Parrey, Ryan C. (Disability Studies Quarterly, 2016)
Disorienting encounter with disability are those in which the meaning of disability is an open question, and in which our relation to it is questionable. This essay explores the relationship between disability and disorientation on conceptual but also concrete levels. First, I examine the connection between disability and disorientation within disability studies. Second, I provide a preliminary sketch of disorientation through what I call ontic disruption and ontological disorientation. Third, I take up Leder's (1990) articulation of bodily disappearance and embodied dysappearance to address ableist violence. Finally, I develop the notion of dysorientation — a prolonged, persistent or recurrent sense of disorientation — as a useful concept for understanding experiences of ableism but also as a significant meeting point between impairment and disability.